DEVELOPMENT, VALIDATION AND RESOLVING MASS BALANCE ISSUE BY USING ALTERNATIVE OXIDIZING REAGENTS FOR THE DETERMINATION OF METFORMIN HYDROCHLORIDE IMPURITIES IN API AND PHARMACEUTICAL DOSAGE FORMS - Raghava Raju, T.V.; Jagan mohan, T.S.S.; Bhavani prasad, S.V.S.G.; Suresh Kumar, P.; Someswara Rao, N.; Mrutyunjaya Rao, I. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
A novel, sensitive, stability indicating RP-HPLC method has been developed for the quantitative estimation of Metformin Hydrochloride impurities in both bulk drugs and pharmaceutical dosage forms. Effective chromatographic separation was achieved on a C8 stationary phase with simple mobile phase combination delivered in a isocratic mode and quantitation was by ultraviolet detection at 218 nm. The mobile phase consists mixture of buffer and methanol delivered at a flow rate of 1.0 ml/min. Regression analysis showed an r value (correlation coefficient) grater than 0.999 for Metformin Hydrochloride and its impurities.Â  Mass balance issue was observed in peroxide stress and resolved by using alternative oxidizing reagents. The developed method was validated as per ICH guidelines and found to be linear, accurate, precise, specific, robust and rugged. Keywords: Metformin Hydrochloride, Impurities, Validation, RP-HPLC, ICH guidelines